2008
DOI: 10.1136/jmg.2008.057570
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of the Li-Fraumeni syndrome: an update from the French LFS families

Abstract: We have performed an extensive analysis of TP53 in 474 French families suggestive of Li-Fraumeni syndrome (LFS), including 232 families fulfilling the Chompret criteria. We identified a germline alteration of TP53 in 82 families (17%), in 67/232 of the families fulfilling the Chompret criteria (29%) and in 15/242 which did not fulfil these criteria (6%). Most of the alterations corresponded to missense mutations (67%), and we identified in four families genomic deletions removing the entire TP53 locus, the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
148
1
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(159 citation statements)
references
References 27 publications
8
148
1
2
Order By: Relevance
“…First, missense mutations in DBMs appear to carry the most severe phenotype (early onset cancer) and to be more deleterious than mutations that occur outside DBMs or mutations that delete the whole p53 protein. 10 These results also are supported in mouse model, including both knock-out 32 and knock-in studies 33 (the latter studies revealed a higher propensity for sarcomas and more frequent metastatic disease). These observations are compatible with the notion that the most severe germline TP53 mutations are those that induce the production of a mutant p53 protein with dominant-negative functions.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…First, missense mutations in DBMs appear to carry the most severe phenotype (early onset cancer) and to be more deleterious than mutations that occur outside DBMs or mutations that delete the whole p53 protein. 10 These results also are supported in mouse model, including both knock-out 32 and knock-in studies 33 (the latter studies revealed a higher propensity for sarcomas and more frequent metastatic disease). These observations are compatible with the notion that the most severe germline TP53 mutations are those that induce the production of a mutant p53 protein with dominant-negative functions.…”
Section: Discussionmentioning
confidence: 69%
“…Among patients who are referred for testing using these criteria, 29% have TP53 germline mutations identified. 10 Although detailed, population-based data are lacking, it is believed that de novo TP53 mutations occur in approximately 1 of every 5000 births in the general Western population. 11 A more recent study, however, suggests that the frequency of germline TP53 mutations in the general population probably is likely 1 in 20,000.…”
Section: Introductionmentioning
confidence: 99%
“…Missense mutations within Ex4-9 generally accelerate first tumor onset, compared with all other p53 alterations including large and small in-frame deletions, splice and nonsense mutations and mutations outside Ex4-9. 16,17 Given our differential mouse results, we therefore evaluated whether such a genotype-phenotype difference also exists among humans with R248Q/ þ , G245S/ þ and null/ þ heterozygous germline mutations. Although analysis of mutant/ þ mouse models was not performed in this study, the majority (56%) of tumors from Li-Fraumeni syndrome patients undergo a loss of heterozygosity (LOH) event at the site of the germline mutation during tumorigenesis to eliminate the wild-type allele, 18 resulting in tumors with one of the two mutant p53 configurations reported here (mutp53/ À or mutp53/mutp53).…”
Section: Resultsmentioning
confidence: 99%
“…116 For these guidelines, we are adopting a combination of the Eeles and revised Chompret criteria. 117 In two large studies, 29% 118 and 35% 112 of individuals who met the original, slightly more restrictive, Chompret criteria 119 had a TP53 mutation. However, 14% of individuals who met the looser Eeles criteria also had a TP53 mutation.…”
Section: Li-fraumeni Syndrome (Omim 151623)mentioning
confidence: 99%